Developmental Changes in Drawing Production Under Different Memory Demands in a U.S. and Chinese Sample. - Long, Bria; Wang, Ying; Christie, Stella; Frank, Michael C.; Fan, Judith E. (Developmental Psychology, 2023)
Children's drawings of common object categories become dramatically more recognizable across childhood. What are the major factors that drive developmental changes in children's drawings? To what degree are children's drawings a product of their changing internal category representations versus limited by their visuomotor abilities or their ability to recall the relevant visual information? To explore these questions, we examined the degree to which developmental changes in drawing recognizability vary across different drawing tasks that vary in memory demands (i.e., drawing from verbal vs. picture cues) and with children's shape-tracing abilities across two geographical locations (San Jose, United States, and Beijing, China). We collected digital shape tracings and drawings of common object categories (e.g., cat, airplane) from 4- to 9-year-olds (N = 253). The developmental trajectory of drawing recognizability was remarkably similar when children were asked to draw from pictures versus verbal cues and across these two geographical locations. In addition, our Beijing sample produced more recognizable drawings but showed similar tracing abilities to children from San Jose. Overall, this work suggests that the developmental trajectory of children's drawings is remarkably consistent and not easily explainable by changes in visuomotor control or working memory; instead, changes in children's drawings over development may at least partly reflect changes in the internal representations of object categories. Public Significance Statement: The present study examined developmental changes in children's drawings of common object categories from 4 to 9 years of age. The findings suggest relative consistency in the developmental trajectory of drawing recognizability across two different sites (San Jose, United States, and Beijing, China) and two different drawing tasks (verbal vs. picture cues). The digital drawings and stroke-by-stroke records are made available as a resource for future work.